2012
DOI: 10.1371/journal.pone.0042805
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Specific Over-Expression of Epidermal Growth Factor Receptor 2 (ErbB2) Induces Pro-Survival Pathways and Hypertrophic Cardiomyopathy in Mice

Abstract: BackgroundEmerging evidence shows that ErbB2 signaling has a critical role in cardiomyocyte physiology, based mainly on findings that blocking ErbB2 for cancer therapy is toxic to cardiac cells. However, consequences of high levels of ErbB2 activity in the heart have not been previously explored.Methodology/Principal FindingsWe investigated consequences of cardiac-restricted over-expression of ErbB2 in two novel lines of transgenic mice. Both lines develop striking concentric cardiac hypertrophy, without heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 75 publications
4
63
0
Order By: Relevance
“…Our previous studies on ErbB2 overexpression in the heart showed a concurrent upregulation of EGFR (62), as this phenomena has been observed in cancer cells with ErbB2 upregulation (22,28). Furthermore, in addition to ErbB2, EGFR is also known to bind and activate Abl kinases in breast cancer cells; consequently, the activities of EGFR cannot be excluded here (59).…”
Section: Erbb2 Overexpression Upregulates Nonreceptor Tyrosine Kinasementioning
confidence: 95%
See 4 more Smart Citations
“…Our previous studies on ErbB2 overexpression in the heart showed a concurrent upregulation of EGFR (62), as this phenomena has been observed in cancer cells with ErbB2 upregulation (22,28). Furthermore, in addition to ErbB2, EGFR is also known to bind and activate Abl kinases in breast cancer cells; consequently, the activities of EGFR cannot be excluded here (59).…”
Section: Erbb2 Overexpression Upregulates Nonreceptor Tyrosine Kinasementioning
confidence: 95%
“…However, the specific role of ErbB2 as it is related to ROS-scavenging mechanisms has not been defined, and critical in vivo studies to investigate how ErbB2 affects ROS defenses and mitochondrial function in the heart have not been done, largely because ErbB2 knockout mice die prematurely, precluding the study of specific mechanisms of cardiac protection. We therefore sought to further investigate the possible protective role of cardiac ErbB2 upregulation using a recently developed transgenic murine model that selectively overexpresses ErbB2 in cardiomyocytes (62). Specifically, we used this transgenic mouse model to examine the role of ErbB2 upregulation on mitochondrial function and antioxidant defense mechanisms in the heart.…”
Section: This Is the First Study On Erbb2 Overexpression In The Heartmentioning
confidence: 99%
See 3 more Smart Citations